Anterior intradural tumors of spine in children: endoscopy guided resection with neurophysiological monitoring by posterior approach - Gepp , Ricardo de Amoreira (2019)
Introduction: Anterior intradural tumor of the spine is a challenge to the surgeon, especially in children. The use of the endoscope in intradural spinal tumors surgery is still poorly described. The association between spinal endoscopy and neurophysiological monitoring allows better tumor visualization and lower risk of retraction of the spinal cord, decreasing the neurological risk. Methods:  The authors described the posterior approach to tumor resection. The medical records from two cases were described. Results: In the first case one dermoid tumor anterior to spinal cord was completed resected after endoscopy help. The second patient had one anterior tumor and the endoscopy was used to help gross total resection. Conclusion: Microsurgery assisted by endoscopy is a safe and effective method to control resection of intradural tumors, and associated with neurophysiological monitoring becomes a secure method of approach this type of tumor in children.